(untitled) (Veterinary Science, 2026)
In the design of probiotic formulations, preservation of microorganism’s viability is the most important parameter to evaluate at the time of administration. In this study, the impact of spray-drying on the preservation of probiotic strains isolated from pig feces: Limosilactobacillus reuteri CRL2222, Lactobacillus amylovorus CRL2225 and Lactobacillus johnsonii CRL2229 was studied, by using a previously formulated protectant mix. The three probiotic strains displayed high resistance to spray-drying operating conditions and subsequent storage, showing survivability’s between 92.9 and 94.7%; probiotic powders exhibited low water activity (aw:0.2) and moisture content ranging from 3.3±0.16 and 3.8±0.46. The used trehalose/maltodextrin/soy protein/sodium glutamate/calcium phosphate protectant mix showed high thermal protection during the process, allowing high final viability. When probiotic functionality of the strains was evaluated, hydrophobic character was maintained. Thus, it may be highlight that both viability and functionality of probiotics was preserved after spray-drying, characteristics that are strain-specific.